Identification of an atypical replicative genetic element in Rhodococcus jostii RHA1 - Acedos, Miguel G.; de la Torre, Isabel; Barriuso, Jorge; García, José L. (Frontiers in Microbiology, 2025)
By exploring the use of plasmids to confer Rhodococcus jostii RHA1 the possibility of utilizing xylose to produce lipids we have observed that the plasmid used was not always maintained in the transformants as expected. Instead, we observed an illegitimate integration of the antibiotic resistance gene from the plasmid into the recombinant cells. Genome sequencing of the transformants has provided evidence that this illegitimate integration is not size-, site-or sequence-specific. But even more surprising, genome sequencing revealed the presence of an unexpected circular multicopy replicative element (75–80 kb) that appears to be excised from the chromosome as a consequence of the stress generated by the antibiotic used in the selection process. The excised fragment does not contain any of the typical features of genomic islands. These results provide evidence that the genome of this oleaginous strain is more plastic than initially anticipated and our findings open the option of developing new ways to genetically modify this strain by using illegitimate recombinant approaches. But even more remarkably, the discovery of this atypical replicative element raises new questions about the existence of novel mechanisms of evolution in bacteria.